Interview with Prof. Theo van Boven - Croonen, Jef; Arends, Jan Jippe (Utrecht Journal of International and European Law, 2010)
Professor van Boven has been, amongst others, director of the United Nations' Division for Human Rights, UN Special Rapporteur on the Right to Reparation to Victims of Gross Violations of Human Rights, UN Special Rapporteur on Torture, a member of the International Commission of Jurists and has been the first registrar of the International Criminal Tribunal for the former Yugoslavia.